Experience in bariatric and metabolic surgery Obesity, Bariatric and Metabolic Surgery Program at Maciel Hospital - Lapi, Silvana; Perdomo, Mauro; Brandolino, Soledad; Altamirano, Emilia; Hernández, Rodrigo; Bentancor, Marisel; Bruno, Gustavo; Vaucher, Andrea; Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2025)
Contributors: Drs. Jessica Godoy; Gregory Marrero; Belén Borges. Introduction: The World Health Organization (WHO) has established that obesity is a non-communicable epidemic and the largest disease worldwide. Overweight and obesity are among the ten main health risk factors. Uruguay appears to be one of the countries where the percentage of this disease has grown most rapidly in the last ten years. Metabolic and Bariatric Surgery (MBS) has achieved benefits in the control of this disease and its comorbidities. Objective: To determine the effectiveness of bariatric surgery in morbidly obese patients enrolled in the Obesity, Bariatric, and Metabolic Surgery Program at Maciel Hospital, from January 1, 2016, to December 31, 2024. To assess the surgical procedures and the responses to the various comorbidities. To report the results. Material and methods: Retrospective analysis of a prospectively collected database, including patients treated by the Obesity, Bariatric and Metabolic Surgery Program team at Maciel Hospital. Results: A total of 399 patients were analyzed, followed at one year. The mean age was 40.08 years, and 84.2% were women. The mean BMI at the start of the program was 52.33. A statistically significant reduction was observed in BMI, diabetes mellitus, hypertension, dyslipidemia, and obstructive sleep apnea-hypopnea syndrome one year postoperatively. Significant differences were found in the variables studied when comparing sleeve gastrectomy and Roux-en-Y gastric bypass. Conclusions: MBC is effective in controlling obesity and its comorbidities, making it an effective therapeutic tool.